THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP, WORK ETHOS, AND ORGANIZATIONAL CULTURE ON TEACHER PERFORMANCE - Mohammad Amas Lahat; Amas Sari Marthanti; Jaka Santosa (Jurnal Ekonomi, 2022)
This study examines and analyzes the effect of transformational leadership, work ethic, and organizational culture on teacher performance. The study was conducted on teachers at private vocational schools in South Jakarta using a Likert scale questionnaire. The collected data is processed using the SmartPLS version 3.0 application. The results show that organizational culture has a significant effect on teacher performance. Organizational culture can create situations that can encourage teachers to improve their performance. Transformational leadership does not affect teacher performance. A too-short change process can cause this insignificant impact. Change is a gradual process requiring persistent effort, and work ethic significantly affects teacher performance. Work ethic has been proven to encourage someone to be enthusiastic to do work, strive to improve the quality of work, and always think positively about what is done to get maximum work results.